Systemic antibiotic use for nonbacterial dermatological conditions among referring providers. (9th March 2018) - Haynes, Dylan; Lasarev, Michael; Keller, Jesse
Abstract: Background: As usage of systemic antibiotic therapies has increased, so too has bacterial resistance. Antibiotic stewardship thus rests in part on judicious use of empiric treatment. The specific factors which underlie erroneous prescription patterns for dermatological conditions have not yet been well elucidated. Objective: The objective of this study was to identify whether a predefined group of dermatologic conditions under the heading "pseudobacterial"—including eczematous conditions, arthropod assault, herpes zoster, neurodermatoses, autoimmune blistering disorders, and neutrophilic dermatoses—are associated with increased antibiotic use prior to dermatology referral. Methods: This observational prospective study included 207 participants referred to an academic dermatology referral center for acute skin conditions which were ultimately deemed to be of a nonbacterial cause. Preceding antibiotic prescription, final diagnosis, and patient, and provider characteristics were reviewed. Results: Antibiotic prescription were provided to 31/207 individuals. Patients with pseudobacterial diagnoses (66/207 individuals) had 4.79 (95% CI, 2.03–11.3) times the odds of empiric antibiotic treatment compared to all others. Rural referring providers (OR, 8.54; 95% CI, 1.81–40.3) and referring providers in areas with a low density of medical specialists (OR, 3.70; 95% CI, 1.43–10.0) also displayed increased odds of empiric antibiotic prescription for nonbacterial skin disease, though the former finding may be limited by the low number of rural vs. urban providers (7 vs. 200) included in the study. Conclusion: Patients with noninfectious pseudobacterial dermatological conditions experienced greater odds for unnecessary exposure to antibiotics. Additional independent risk factors included rural settings and diminished access to specialist care.